2018
DOI: 10.3389/fphys.2018.01684
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Transporter Activity-Related Genetic Polymorphisms Are Associated With Steroid-Induced Osteonecrosis of the Femoral Head: An Updated Meta-Analysis Based on the GRADE Guidelines

Abstract: Aims: The purpose of this study was to assess the relationship between genetic variants and steroid-induced osteonecrosis of the femoral head (SONFH) in steroid use populations.Methods: We searched the public databases up to April 15, 2018. This study analyzed only the single-nucleotide polymorphisms (SNPs) that have appeared in more than three studies and assessed the level of evidence by classifying the outcomes according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The results showed that ABCB1 rs1045642 could reduce the occurrence of SONFH but had a very low level of evidence. ApoB rs693 and rs1042031 mutations increased the risk of SONFH and had a moderate level of evidence [46]. The results of our study are essentially the same as those of the above two studies, except for rs2032582.…”
Section: Discussionsupporting
confidence: 82%
“…The results showed that ABCB1 rs1045642 could reduce the occurrence of SONFH but had a very low level of evidence. ApoB rs693 and rs1042031 mutations increased the risk of SONFH and had a moderate level of evidence [46]. The results of our study are essentially the same as those of the above two studies, except for rs2032582.…”
Section: Discussionsupporting
confidence: 82%
“…In steroid-induced FHON, ApoB has genetic variants rs693 and rs1042031 with significant p values for the main effect [ 35 ]. Particularly, rs1042031 showed a very significant result in the dominant genetic model with an odds ratio of 2.90 in various ethnicities and an odds ratio of 4.81 in Asians.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the presence of the T allele had protective effects [ 60 ]. Rs1042031 is also known as important for regulating the ApoB binding capacity to cholesterol receptors [ 35 ]. In this study, rs693 and rs1042031, which are polymorphisms of ApoB, each showed high significance in the dominant models.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that rs964184 had negative associations with serum APOA levels but had no associations with insulin resistance in a large cross-sectional study. APOB rs1042031(EcoRI) has been widely used to study coronary heart disease (CHD) [39] and Steroid-Induced Osteonecrosis of the femoral head (SONFH) [40]. They found APOB rs1042031 confers a moderate risk for CHD [39] and increase the SONFH risk with moderate levels of evidence.…”
Section: Discussionmentioning
confidence: 99%